The idiot - Batuman, Elif (Penguin, 2017)
"A portrait of the artist as a young woman. A novel about not just discovering but inventing oneself. The year is 1995, and email is new. Selin, the daughter of Turkish immigrants, arrives for her freshman year at Harvard. She signs up for classes in subjects she has never heard of, befriends her charismatic and worldly Serbian classmate, Svetlana, and, almost by accident, begins corresponding with Ivan, an older mathematics student from Hungary. Selin may have barely spoken to Ivan, but with each email they exchange, the act of writing seems to take on new and increasingly mysterious meanings. At the end of the school year, Ivan goes to Budapest for the summer, and Selin heads to the Hungarian countryside, to teach English in a program run by one of Ivan's friends. On the way, she spends two weeks visiting Paris with Svetlana. Selin's summer in Europe does not resonate with anything she has previously heard about the typical experiences of American college students, or indeed of any other kinds of people. For Selin, this is a journey further inside herself: a coming to grips with the ineffable and exhilarating confusion of first love, and with the growing consciousness that she is doomed to become a writer. With superlative emotional and intellectual sensitivity, mordant wit, and pitch-perfect style, Batuman dramatizes the uncertainty of life on the cusp of adulthood. Her prose is a rare and inimitable combination of tenderness and wisdom; its logic as natural and inscrutable as that of memory itself.The Idiot is a heroic yet self-effacing reckoning with the terror and joy of becoming a person in a world that is as intoxicating as it is disquieting. Batuman's fiction is unguarded against both life's affronts and its beauty--and has at its command the complete range of thinking and feeling which they entail"-- Provided by publisher.